Humans, apes, and Chinese fossils : new implications for human evolution : a seminar presented to the Department of Anatomy, University of Hong Kong - Oxnard, Charles E., 1933- (Occasional papers' series (Hong Kong University Press), 1985)
The Hong Kong University Press Occasional Paers' Series is an entirely new series of monographs encompassing the best lectures presented to the University of Hong Kong in recent times.The series will cover all disciplines concomitant to full University studies.Items for inclusion in the series will be selected by the University Press Committee, whose decision is final.